PENGENALAN PAYMENT GATEWAY SEBAGAI ALTERNATIF PEMBAYARAN DAN DIGITALISASI PENCATATAN KAS PADA DYARALARASATI WEDDING ATTIRE JOMBANG - Irea Arrahima; Nurianah; Beni Sucipto; Dwi Ermayanti Susilo (COMVICE: Journal Of Community Service, 2026)
This community service program was implemented in response to the low adoption of digital financial systems among MSMEs in the service sector, particularly wedding attire rental businesses, which have high transaction volumes but still rely on cash payments and manual cash recording. This situation risks operational inefficiencies, recording errors, and limited data-driven decision-making. This activity aims to introduce payment gateway-based payment alternatives and implement digital cash recording at the Dyaralarasati Jombang Wedding Attire. The service method was implemented through outreach, application training, direct mentoring, and achievement evaluation. An integrative approach that connects digital payment acceptance systems with daily cash recording in a single financial management flow demonstrates increased partner understanding of selecting a payment gateway that suits the nature of the business and the ability to perform more accurate, transparent, and real-time digital cash recording. This implementation is expected to strengthen the financial resilience of MSMEs and enhance their business readiness for the digital economy ecosystem.